MANAJEMEN PENDIDIKAN SEKOLAH INKLUSI DI SEKOLAH DASAR MUHAMMADIYAH MBAYEN, KALASAN, SLEMAN, YOGYAKARTA (JURNAL ILMIAH TUT WURI HANDAYANI, 2015)
This research is aimed to describe the implementation of inclusive school management in elementary school Muhammadiyah Mbayen, Kalasan, Sleman, which includes planning, implementation and evaluaton of 8 National Education Standards.This research used a qualitative approach, where the place of study was in elementary school Muhammadiyah Mbayen, Kalasan, Sleman regency. Researcher served as instrument in the research. Data sources of this study consisted of principal, teachers and school supertendent. Techniques of data collection used interview, observation, and documentation. Techniques of data collection in this research were done since the beginning of the study. The data were analyzed and set forth in meaningful word qualitatively. Test of the data validity used the test of data credibility that fulfils validity, reliability, and objectivity. In addition to using the increased persistence, authors used triangulation credibility test. Data validity checking techniques was using triangulation method to test the credibility of the data.The results of this study concluded that the public elementary school Muhammadiyah Mbayen in implementing management inclusive school has tried as far as possible 8 National Education Standards which include: content standards process standards, graduation standards, standards of teachers and education staff, facilities and infrastructure standards, management standards, financial standards and assessment standards, and regulation of national education minister (Permendiknas) Number 70 in 2009. The implementation of the management begins with plan that includes 8 standards. Implementation of its activities was also referring to the plans that have been made. It stands out from the implementation of the 8 standard is the standard process and standard financial. Monitoring and evaluation carried out by principals, but school supervisors also played an active role. In addition to the results of monitoring and evaluation were also reported to the relevant agencies. The results of the evaluation and monitoring were used as basis in determining the policies and subsequent plans either by the principal, superintendent, or by the related department.